Cervicofacial Actinomycosis in the Pediatric Population: Presentation and Management. (March 2022) - Gandhi, Karan; van der Woerd, Benjamin D.; Graham, M. Elise; Barton, Michelle; Strychowsky, Julie E.
Background: Infection caused by Actinomyces species is a rare cause of head and neck infection in children. This chronic cervicofacial infection can present with localized swelling, abscess formation, sinus drainage and can be complicated by osteomyelitis. Methods: Presented are 2 pediatric cases of secondary actinomycosis in the context of congenital lesions: 1 patient with a previously excised preauricular sinus and another with a persistent sublingual mass. A comprehensive literature search was conducted for reported cases of pediatric actinomycosis in the cervicofacial region. Results: Both cases presented were successfully treated with a combination of complete surgical excision of the lesions and prolonged antibiotic therapy. Thirty-four pediatric cases of cervicofacial actinomycosis are reviewed, 2 presented herein, and 32 from the published literature. There was equal gender distribution and the median age was 7.5 years. The most common site for infection was the submandibular area. Four (12%) of cases arose in pre-existing congenital lesions. Most patients were treated with penicillin-based antibiotics for a median duration of 6 months following surgical excision or debridement. Conclusions: Actinomycosis is a rare infection of the cervicofacial region; secondary infections arising from congenital lesions of the head and neck are even more rare. A previously excised pre-auricular sinus and a sublingual dermoid cyst are not previously reported sites of infection. Actinomycosis should be suspected in chronically draining sinuses of the head and neck region and confirmed through anaerobic culture. Osteomyelitis is a potential complication and magnetic resonance (MR) imaging is warranted. Long-term antibiotic therapy with a penicillin-based antibiotic and surgical excision should be considered.